(3eONd ddJSjjQ CSGSjGJ,hXGFa,JbfjGJ (B:s (3GdJSjjQ hGdJfXje hGdefTCI (B((3L(B1) /s - (3GdWjH, eMeO Qajbs ((3GdLRGFQ(B: s (3OjhGf GdeWHhYGJ GdLGeYjI(B, s, 2006)
(3CSGSjGJ Yf GdJSjjQ hGdJfXje hGdefTCI,GdJYQja HGdJSjjQ hHWHjYI Yed GdeSjQ,GdJfXje GdJbdjOj,fbO GdJfXje GdJbdjOj,hGdEJLGgGJ GdMOjKI,GdgjcdI GdhXGFajIdefTCI GdCYeGds
(3HHdjhZQGajG(B:(3U(B.221s
Keywords: (3GdEOGQIs; (3GdJfXjes